Early Childcare, Child Cognitive Outcomes and Inequalities in the UK - Daniela Del Boca; Daniela Piazzalunga; Chiara D. Pronzato (Institute for the Study of Labor (IZA), 2016)
The objective of this research is to explore the impact of early childcare on child cognitive outcomes. We utilize the Millennium Cohort Survey (MCS) for the United Kingdom, which provides very detailed information about several modalities of childcare as well as several child outcomes. In our empirical analysis, we estimate the association between formal childcare and child cognitive outcomes, allowing the effect of formal childcare to be different for children from different family backgrounds, controlling for a large number of variables (regarding the child, the mother, the father, the household). In a second step, we simulate how an increase in formal childcare attendance can affect inequalities across children. Our results show that childcare attendance has a positive impact on child cognitive outcomes, which are stronger for children from low socio–economic background.
Keywords: J13; H75; 330; child care; child outcomes; inequalities